FINANCIAL MANAGEMENT IN THE SPORT INDUSTRY - Brown, Matthew T.; Rascher, Daniel A.; Nagel, Mark S.; McEvoy, Chad D., 1971- (Routledge, 2021)
"Now in a fully revised and updated third edition, this essential textbook introduces the fundamentals of sport finance and sound financial management in the sport industry. It is still the only textbook to explain every aspect of finance from the perspective of the sport management practitioner, explaining key concepts and showing how to apply those concepts in practice in the context of sport. The text begins by covering finance basics and the tools and techniques of financial quantification, using industry examples to apply the principles of financial management to sport. It then goes beyond the basics to show how financial management works specifically in the sport industry. Discussions include interpreting financial statements, debt and equity financing, capital budgeting, facility financing, economic impact, risk and return, time value of money, and more. The final part of the book examines financial management in four sectors of the industry: public sector sport, collegiate athletics, professional sport, and international sport. It provides an in-depth analysis of the mechanics of financial management within each of these sport sectors. Useful features, such as sidebars, concept checks, practice problems, case analysis and case questions will help students engage more deeply with financial techniques and encourage problem-solving skills. This new edition includes a completely new chapter on international sport, reflecting the globalized nature of the modern sport industry, as well expanded coverage of current issues such as digital media finance, recent legal cases affecting collegiate sport, and the central importance of collective bargaining. Financial Management in the Sport Industry is an essential textbook for any undergraduate or postgraduate course in sport finance, and an invaluable supplement to any course in sport business or sport management. It is also an important reference for all sport management practitioners looking to improve their understanding of finance"--